IDENTIFIKASI MORFOLOGI JAMUR YANG BERASOSIASI DENGAN PENYAKIT BUSUK PELEPAH PADI - Ivayani; Nuraini, Safira (Fakultas Pertanian Universitas Janabadra, 2025)
Rice sheath rot disease is one of the diseases that can significantly reduce rice plant productivity. This disease is complex as it can be caused by various types of pathogens. This study aimed to identify fungi associated with rice sheath rot disease based on morphological characteristics. Symptomatic rice sheaths were collected from several rice production centers in Lampung Province, followed by isolation and morphological characterization on the Potato Dextrose Agar (PDA) medium. Morphological identification was conducted based on macroscopic and microscopic characteristics, which were compared with relevant literature. The results of the study identified several fungi associated with rice sheath rot disease, including Sarocladium oryzae, Sarocladium sparsum, Fusarium bubalinum, Fusarium hainanense, Alternaria sp., and Curvularia sp.